Archaeological Economics of Ratu Baka In Quran 3.96 Bibakkah With 72 Moving Stupas According to Hahslm 472319 And Plural Code 12 Covid Era - R Mochamad A (Proceeding International Conference on Malay Identity, 2021)
Abstract: The purpose of this research is to analyze the archeology of the 72 stupa houses built by Ratu Baka according to the Quran Surah Ali Imran [3]: 96 with the word Bibakkah in the perspective of Hahslm 472319 in the Covid economic era. The Baka temple area has a main gate with 5 doors and 3 doors with an empty space of 25 hectares. The objects of this study are 72 stupas and 3.96 verses of the Quran. The scope of the research consists of the Ratu Baka Area and Borobudur Temple. This study was carried out by studying literature through journals, books and electronic media. The methodology used is analytical descriptive using reflexivity and similarity methods in the dynamic approach referring to the verses of the Koran. Hahslm 472319's perspective is used as a benchmark that the building also reflects the meaning of worship in the creation of the universe. The results obtained are buildings that appeared as the beginning of civilization in the medieval era between the prophets Adam and the prophet Muhammad in the form of 72 stupas. The 72 small temples and 1 large stupa were built by Queen Baka which is written in the Quran Surah Ali Imran [3]: 96 as the word Bibakkah. Bi means by and bakkah is a person's name, namely bakka with the ending h indicating the female gender is Ratu Baka. There is a word placed which is interpreted as a result of being moved or floating in nature with no foundation embedded at the bottom. The buildings made by Bakkah are 72 small stupas and 1 large stupa. The letter number and verse number have similarity with the existing stupa structure. Three similar floors with letter number 3, seventy-two similar stupas with verse number 9. And the number of stupas per floor, namely 16, 24, 32, has similarity with a factorization of 6, namely 1+2+3=6 and 6+4+2=12 , where 6 and 12 are multiples of 6. The conclusion of this study is that Ratu Baka and Bakkah are the same individual reinforced by Baka stupas numbering 72 which were codified in 396. Social humanity is experiencing adaptation to the new normal in the covid pandemic which has affected the global economy . Keywords: bakkah, stupa, quran, hahslm, 472319